Pengaruh Ketersediaan Jurnal Online Proquest Terhadap Pemenuhan Kebutuhan Informasi Pemustaka di Perpustakaan Universitas Negeri Padang - Siti Azizah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
This study aims to determine how the influence of the availability of online proquest journals on meeting the information needs of users in the Padang State University Library. This research is a qualitative research with descriptive analysis method, a method that describes data to get conclusions in general. The data collection technique in this research is to use the interview method. The results of this study are the availability of online proquest journals in the UNP Library according to the library users' perception is good and the library users claim that they get advice from lecturers so that they look for sources of reference to make lecture assignments from these online proquest journals not from the library. Library users have used it well as a source of reference to assist in making college assignments. The influence of the Proquest Journal on the information that is needed by the user is quite influential in meeting the information needs because this journal provides an up-to-date and accurate source of information to be used as a reference in making college assignments and in completing research.